Qualidade de vida de atletas de voleibol sentado - GONZAGA, Raqueline Trindade (2023)
We know that the practice of physical activity brings several health benefits and has been an important ally in improving the quality of life of people with disabilities. According to the World Health Organization (WHO), quality of life is the perception of the individual in relation to his position in life, in the cultural context and in the system of values in which he lives, and also in relation to his goals, expectations, standards. and concerns. Therefore, this study aimed to evaluate the quality of life of sitting volleyball athletes, from the ACEAB project. For this, a field study was developed. Data collection used the WHOQOL-Bref questionnaire as an instrument, applied to 13 male athletes, who practiced sitting volleyball, aged between 29 and 52 years. The information was analyzed descriptively through graphs and statistics. The results obtained demonstrate that sitting volleyball had a positive influence on the psychological and social aspects of the quality of life of the athletes who participated in the research.